CONTEXT IN PRAGMATICS - Indrawati, - (Faculty of Languages Ã¢â¬â¹Ã¢â¬â¹and Arts, State University of Semarang, 2009)
People carry out almost all social behaviors through language, either spoken or written. The language to be used needs rules and principles; and when it comes to see language from a socio-cultural perspective, and consider the Ã¢â¬Ëworlds of usersÃ¢â¬â¢ incorporating the context or Ã¢â¬Ëhuman conditionÃ¢â¬â¢, people refer to the pragmatic use of it, which means that Pragmatics is the study of a context-dependent language. People owe their respects to great many linguists and experts in Pragmatics for their various expertises in this field to explain Ã¢â¬Ëhow the language operates in force of contextually implied conditionsÃ¢â¬â¢. With this view, the writer of this paper attempts to learn the important relationship between context and Pragmatics.